Acute myocardial infarction: Quality of care in rural Alberta - Domes, Trustin (College of Family Physicians of Canada, 2006)
OBJECTIVE: To assess the quality of care of acute myocardial infarction (AMI) in a rural health region. DESIGN: Clinical audit employing multiple explicit criteria of care elements for emergency department and in-hospital AMI management. The audit was conducted using retrospective chart review. SETTING: Twelve acute care health centres and hospitals in the East Central Health Region, a rural health region in Alberta, where medical and surgical services are provided almost entirely by family physicians. PARTICIPANTS: Hospital inpatients with a confirmed discharge diagnosis of AMI (ICD-9-CM codes 410.xx) during the period April 1, 2001, to March 31, 2002, were included (177 confirmed cases). MAIN OUTCOME MEASURES: Quality of AMI care was assessed using guidelines from the American College of Cardiology and the American Heart Association and the Canadian Cardiovascular Outcomes Research Team and Canadian Cardiovascular Society. Quality of care indicators at three stages of patient care were assessed: at initial recognition and AMI management in the emergency department, during in-hospital AMI management, and at preparation for discharge from hospital. RESULTS: In the emergency department, the quality of care was high for most procedural and therapeutic audit elements, with the exception of rapid electrocardiography, urinalysis, and provision of nitroglycerin and morphine. Average door-to-needle time for thrombolysis was 102.5 minutes. The quality of in-hospital care was high for most elements, but low for nitroglycerin and angiotensin-converting enzyme (ACE) inhibitors, daily electrocardiography, and counseling regarding smoking cessation and diet. Few patients received counseling for lifestyle changes at hospital discharge. Male and younger patients were treated more aggressively than female and older patients. Sites that used care protocols achieved better results in initial AMI management than sites that did not. Stress testing was not readily available in the rural region studied. CONCLUSION: Quality of care for patients with AMI in this rural health region was high for most guideline elements. Standing orders, protocols, and checklists could improve care. Training and resource issues will need to be addressed to improve access to stress testing for rural patients. Clinical audit should be at the core of a system for local monitoring of quality of care.